Community Based Cultural Tourism Development Setu Babakan, Jakarta - WIDANINGSIH, T.Titi; DIANA, Rahtika; RAHAYUNIANTO, Arry (Journal of Environmental Management and Tourism; Vol 11 No 2 (2020): JEMT Volume Xi Issue 2(42) Spring 2020, 2020)
The Setu Babakan tourism area has been designated as a Betawi cultural tourism area by the Provincial Government of DKI Jakarta in 2000. Setu Babakan has three tourism objects culture, nature and agro. It has been established as a cultural heritage for more than 15 years, but the level of tourist visits still low. This research will analyze factors of Community-Based Cultural Tourism Development in the Setu Babakan tourism area, both tourism object factors and community participation include several dimensions, (1) objects, (2) access, (3) facilities, (4) participation, (5) support, (6) benefits, (7) revenue. The study was conducted by distributing 81 questionnaires to surrounding community in the area. The results of the MDS analysis in dimensions of the attractions are in the good category of 80.57. Dimensions of access, infrastructure, community support for tourism development, public attitudes towards tourists are in the good categories of 84.64, 80.39, 81.87, and 75.62. Dimension of community participation and benefits perceived by the community is in the unfavorable category of 44.69% and 46.29. Community involvement needs to be increased so it can increase tourist visits. The sustainability of Setu Babakan as a cultural tourism area is maintained because the existence of it can really be felt by the local community.